Le proxénète, cible mouvante des politiques de prostitution - Lilian Mathieu (Genre, Sexualité et Société)
The procurer is a major target of prostitution policies. But this is a moving target, due to the diversity of its modes of existence. The article first evokes the moral existence of the procurer, that is produced in the public discourses about him by organisations and politicians who support the abolition of prostitution. According to them, the procurer is a man, of foreign origin, acting in an organized gang, resorting to violence and manipulation, granted with powers of influence and considerable means in order to preserve his interests, and who gathers enormous profits by the exploitation of his victim’s bodies. The penal existence of the procurer is, for its part, the conclusion of a judiciary labelling process. The observation of trials reveals notable differences between the people who are concretely sentenced for procuring and the figure of the procurer that is invoked by the abolitionists.